EMPOWERING CHILDREN: MEANING, REQUIREMENTS AND IMPORTANCE - Kabuye Uthman Sulaiman, (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2024)
Empowerment is a means to transforming the lives of the people and it encompasses a broad range of things. Therefore, of the core aims of Islam is to empower individuals and societies spiritually, physically, morally and intellectually. This paper is an illuminating insight into an understanding of the concept of empowerment in general and empowerment of children in particular from the perspective of Islam, i.e., the Qur’an and Hadith. It describes how children should be empowered intellectually, emotionally, morally, spiritually and physically. It provides the most essential skills children need to be successful and achieve their life goals and demonstrates how these skills should be developed. The paper serves as a primer to answering some of the questions related to empowerment of children from the standpoint of Islam. This is qualitative research employing descriptive methods with literature review analysis. The primary sources of this paper comprise selected verses from the Qur’an and their exegesis (tafsir) and Hadith, both of which constitute the major source of guidance for Muslims. Its secondary sources consist of books, journals and other materials. The English translation of the selected verses is based on Abdullah Yusuf Ali’s The Meaning of the Holy Qur’an and The Qur’an: English Meanings by Saheeh International because of their simplistic and comprehensive language. Due to the multidimensional use of words in the Arabic language, it is difficult to translate them into one specific word, therefore, we have retained the Arabic concepts but given some of their meanings in the brackets. Our findings indicate that: firstly, empowerment of children is crucial for sustainable living, and; secondly, the aim of empowering children is nurturing power with, meaning creating the conditions whereby power can be shared, power to and power within. It is not about exercising or maximizing their power over others.